2003
DOI: 10.1192/s1749367600007608
|View full text |Cite
|
Sign up to set email alerts
|

Africa: the traumatised continent, a continent with hope

Abstract: Many African countries gained political independence in the 1960s and 1970s and went through difficult times in economic, political and security terms in the 1980s and early 1990s. Mental health services and research were not spared and stagnated or deteriorated during this period. The effects of poor governance, inequitable distribution of resources and environmental degradation conspired with natural and man-made disasters (wars in particular) to drive Africa into an abyss of despair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Factors contributing to psychological trauma and stress include, among other things, violence, imprisonment, torture, rape, displacement, loss of family members, and loss of property. Furthermore, the ripple effects of ongoing wars continue to be felt even years after (Njenga et al, 2003(Njenga et al, , 2006. For example, the Rwandan genocide of 1994 resulted in the loss of life of about 800 0000 people within 100 days and 4 million people displaced.…”
Section: Psychological Trauma and Stress (Invisible Injuries)mentioning
confidence: 99%
“…Factors contributing to psychological trauma and stress include, among other things, violence, imprisonment, torture, rape, displacement, loss of family members, and loss of property. Furthermore, the ripple effects of ongoing wars continue to be felt even years after (Njenga et al, 2003(Njenga et al, , 2006. For example, the Rwandan genocide of 1994 resulted in the loss of life of about 800 0000 people within 100 days and 4 million people displaced.…”
Section: Psychological Trauma and Stress (Invisible Injuries)mentioning
confidence: 99%
“…Finally, studies focused on cultural differences regarding the prevalence of stress-related disorders on the African continent are scarce. Previous studies conducted in African countries showed systematically that years of wars, genocide, poverty and natural disasters have been a source of trauma on a massive scale (Neuner et al, 2004; Njenga, Kigamwa, & Okonji, 2003). These studies show that African citizens suffer from a very high level of posttraumatic symptoms (Njenga, Nguithi, & Kang’ethe, 2006) and that these symptoms are also transmitted to the next generation (Shrira, Mollov, & Mudahogora, 2019).…”
mentioning
confidence: 99%